A mixed methods analysis of perceived cognitive impairment in hematopoietic stem cell transplant survivors. Issue 4 (August 2019) - Wu, Lisa M.; Kuprian, Nadia; Herbert, Krista; Amidi, Ali; Austin, Jane; Valdimarsdottir, Heiddis; Rini, Christine
Abstract: Objective: Hematopoietic stem cell transplant (HSCT) survivors may show evidence of objective cognitive impairment; however, perceived cognitive problems and their impact on quality of life are less well-understood. The purpose of this study was to explore HSCT survivors' perceptions of cognitive impairment and its effect on daily life functioning. Method: Sixty-nine autologous and allogeneic HSCT survivors nine months to three years posttransplant experiencing mild survivorship problems completed a brief structured interview regarding perceived cognitive impairment since transplant. Data were coded and content analyzed. The frequency of participants reporting cognitive problems by domain and associations between reports of cognitive problems and age, depressed mood, anxiety, and health-related quality of life were examined. Result: Overall, 49 of the 69 participants (71%) reported cognitive impairments after transplant: 38 in memory (55%), 29 in attention and concentration (42%), and smaller numbers in other domains. There were no significant differences in problems reported by transplant type. Of the 50 participants who worked before transplant, 19 (38%) did not return to work following transplant, with 12 citing cognitive and health problems as being the reason. There were significant associations between reports of cognitive impairment and younger age ( p = 0.02), depressed mood ( p = 0.02), anxiety ( p = 0.002), and health-related quality of life ( p = 0.008). Significance of results: A large proportion of survivors reported cognitive impairment following HSCT that impaired daily life functioning. Perceived cognitive impairment was associated with younger age, greater distress and reduced health-related quality of life.